An Investigation of the Predictive Validity of the TOEFL iBT® Test at an English‐Medium University in Turkey. Issue 1 (6th December 2018) - O'Dwyer, John; Kantarcıoğlu, Elif; Thomas, Carole
Abstract : This study reports on an investigation of the predictive validity of the TOEFL iBT ® test in an English‐medium institution (EMI) in a non‐target‐language context, namely, Turkey. The relationship between TOEFL iBT scores and academic performance was explored in a cohort of 286 undergraduate students, as was the TOEFL iBT's relationship with an institutional English proficiency exam (Certificate of Proficiency in English [COPE]) used as a benchmark for faculty entry. Performance measures included scores on TOEFL iBT and COPE, grade point averages (GPAs) for content and English for academic purposes (EAP) courses over 2 freshman semesters, and freshman language instructor evaluations of students' freshman EAP performance. Correlations between test scores confirmed a moderate to moderately high predictive validity for content course GPAs and English‐language course GPAs, respectively, and for the TOEFL iBT, particularly in technical fields. Instructor evaluations of student performance supported the findings, with fewer deficiencies in academic English skills for students with higher scores on TOEFL iBT. The study concludes that the TOEFL iBT's predictive validity is on par with the institution's own proficiency test and represents a solid performance measure for use in EMIs in a non‐target‐language context. Abstract : Report Number: ETS RR–18‐43